Gone - Dhalia, Heitor, 1970-; Burnett, Allison; Bentley, Wes, 1978-; Seyfried, Amanda; Sunjata, Daniel, 1971-; Carpenter, Jennifer, 1979-; Stan, Sebastian, 1983-; Summit Entertainment; Sidney Kimmel Entertainment (Firm); Lakeshore Entertainment (Firm) ([Universal City, Calif.] : Summit Entertainment, 2012)
When her sister disappears, Jill is convinced the serial killer who kidnapped her two years ago has returned, and she sets out to once again face her abductor.
DVD, region 1, NTSC, widescreen; Dolby Digital 5.1.
Subtitled for the deaf and hard of hearing.
English or Spanish dialogue; Spanish subtitles.
Title from container.
Amanda Seyfried, Daniel Sunjata, Wes Bentley, Jennifer Carpenter, Sebastian Stan.
Cinematographer, Michael Grady ; composer, David Buckley.
Keywords: Kidnapping -- Drama; Serial murderers -- Drama; Sisters -- Drama; Secuestro -- Teatro; Asesinato -- Teatro; Hermanos -- Teatro; Feature films; Thrillers (Motion pictures); Video recordings for the hearing impaired